2014
DOI: 10.1038/jp.2013.170
|View full text |Cite
|
Sign up to set email alerts
|

Great expectorations: the potential of salivary ‘omic’ approaches in neonatal intensive care

Abstract: Among those that require critical care, preterm neonates have the greatest limitations on available blood or body fluids for clinical or research-based assessments. Recent technological advancements have improved our ability to detect genetic, proteomic and microbial material at the nanoscale level, making analyte and biomarker assessment from even the smallest quantities possible. Saliva is a unique body fluid that not only may be noninvasively and repeatedly obtained, but also contains multiple serum compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…The similar trend of the level of phosphorylation (see Figures 3,4,and 6) and the common and highly specific SxE/pS consensus sequence supported the hypothesis that aPRPs, Hst1, and statherin are all substrates of the same kinase. 14 The kinase, working in the Golgi apparatus of granule-secreting cells, was first defined as Golgi casein kinase and for a long time escaped any attempt of purification and structural characterization.…”
Section: Phosphorylationsupporting
confidence: 74%
See 1 more Smart Citation
“…The similar trend of the level of phosphorylation (see Figures 3,4,and 6) and the common and highly specific SxE/pS consensus sequence supported the hypothesis that aPRPs, Hst1, and statherin are all substrates of the same kinase. 14 The kinase, working in the Golgi apparatus of granule-secreting cells, was first defined as Golgi casein kinase and for a long time escaped any attempt of purification and structural characterization.…”
Section: Phosphorylationsupporting
confidence: 74%
“…2−5 Sampling of saliva can be accomplished without pain and stress for the donor, therefore, representing a suitable bodily fluid that may be collected and investigated also in pediatric age. 6 In the last years our group, as well as other ones, investigated the salivary proteome of preterm newborns and subjects in the pediatric age, highlighting striking differences with respect to adults. 7−11 By an integrated top-down/bottom-up platform, we evidenced that human preterm newborn saliva contains more than 40 major salivary proteins either undetectable (according to the detection limit of our analytical method) or detectable in small amount in saliva of adults.…”
Section: Introductionmentioning
confidence: 98%
“…Whether born prematurely or critically ill at term, infants in neonatal intensive care units can produce only small amounts of saliva compared to older populations for which commercially available salivary analysis products have been developed. The need to use emerging technology for biomarker discovery and improved noninvasive monitoring of neonates is great (Romano-Keeler et al 2014). We have found that small modifications to existing protocols and products produce successful results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to conditions shown in Table , applications of salivary diagnostics in a paediatric population include immunological and inflammatory responses to vaccination, as well as cognitive function. In newborns, saliva is used for the enhancement of neonatal diagnosis, assessment of the developmental stage and monitoring of newborns’ health in the neonatal intensive care unit (Romano‐Keeler, Wynn, & Maron, ).…”
Section: Saliva Collectionmentioning
confidence: 99%